Literature for all in Poland? Opportunities and challenges of easy to read standard in special education for the d/Deaf students in primary school - preliminary remarks - Ruta-Korytowska, Karolina; Wrześniewska-Pietrzak, Marta (Frontiers in Education, 2024)
The article discusses the development and challenges of the easy to read (EtR) standard in Poland. The research described in the article aims to evaluate the effectiveness of EtR texts for students with special communication needs, particularly those who are deaf or have aphasia. Conducted as a pilot study, it focuses on whether selected literary texts from the Integrated Educational Platform are understandable for these students and examines the features that may hinder comprehension. The study, carried out during the 2023/2024 school year, involved analyzing selected texts and conducting comprehension assessments with students. The authors chose “The Nightingale” by Hans Christian Andersen and “The Barrel Organ” by Bolesław Prus to gauge understanding among fourth and sixth graders, respectively. The research highlighted that comprehension varies widely within heterogeneous student groups, necessitating further differentiation in text adaptation to meet diverse communication needs. Key findings indicate that vocabulary selection plays a critical role in comprehension, with many terms being unfamiliar or outdated for students. Additionally, low social awareness of EtR’s purpose can lead to stigmatization of easy language, particularly as it is often associated with individuals with intellectual disabilities. The article suggests that more inclusive approaches, such as involving target groups in adapting texts and creating materials suited to different levels of proficiency, could enhance the educational effectiveness of EtR texts. It emphasizes the need for unified guidelines to address the specific needs of various audiences, ensuring better communication and understanding in educational settings.